Analyses of Time Experience in Melancholia on the Ground of Husserl’s Phenomenological Investigations - Valinskaitė, Vijolė (Problemos, 2020)
This paper examines under which conditions melancholic experiences of time (“Time has stopped, nothing happens”, “I cannot see the future”) are possible. In recent phenomenological research on melancholia, melancholic time experiences are analyzed as disturbances in affectivity. However, it is not always clear how the disturbance of time experience might be structurally interrelated with the disturbance in affectivity. This paper focuses on the interrelatedness of temporal synthesis and affectivity in Husserl’s phenomenology. Husserl’s analyses will be used to explain what role affectivity plays in the constitution of the normal daily world experience, and in particular the time experience. Further, it will be shown how a possibility of the disturbance in time experience is already rooted in the most basic layer of constitution.